2022
DOI: 10.1101/2022.02.12.22270883
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiple sclerosis disease-modifying therapies and COVID-19 vaccines: A practical review and meta-analysis

Abstract: Importance: An evidence-based appraisal of the COVID-19 vaccination policies among people with multiple sclerosis (pwMS) with respect to disease-modifying therapies (DMT) is important for our understandings and their further management. Objective: To synthesize the available evidence concerning the effect of DMTs on COVID-19 vaccination immunogenicity and effectiveness. Data Sources: We searched MEDLINE, Scopus, Web of Science, MedRxiv, and Google Scholar from January 2021 until January 2022. Study Selection:… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 89 publications
(188 reference statements)
1
16
0
Order By: Relevance
“…Some of the disease‐modifying therapies (DMTs) for MS suppress the immune system, which results in reduced immune responses to vaccinations 1–25 . In a meta‐analysis of COVID‐19 vaccine studies in MS, post‐vaccine seroconversion rates were 13‐fold lower among patients on B‐cell depleting anti‐CD20 therapies (aCD20) and eightfold lower with S1P receptor modulators (S1P) as compared to patients not on a DMT 24 . Post‐vaccine T‐cell activation post‐vaccine is suppressed with S1P 18,21,22,25 but largely intact with B‐cell depleting therapies even in the absence of antibody responses 4,6,8,10,16–18,21,22,25–27 …”
Section: Introductionmentioning
confidence: 99%
“…Some of the disease‐modifying therapies (DMTs) for MS suppress the immune system, which results in reduced immune responses to vaccinations 1–25 . In a meta‐analysis of COVID‐19 vaccine studies in MS, post‐vaccine seroconversion rates were 13‐fold lower among patients on B‐cell depleting anti‐CD20 therapies (aCD20) and eightfold lower with S1P receptor modulators (S1P) as compared to patients not on a DMT 24 . Post‐vaccine T‐cell activation post‐vaccine is suppressed with S1P 18,21,22,25 but largely intact with B‐cell depleting therapies even in the absence of antibody responses 4,6,8,10,16–18,21,22,25–27 …”
Section: Introductionmentioning
confidence: 99%
“…This issue is of crucial value given the documented hindering effect of some DMTs—namely sphingosine 1-phosphate receptor (S1PR) modulators and anti-CD20 therapies (aCD20) – on proper immunization against COVID-19. 20 , 21–27 Accordingly, the limited available evidence pointed toward lower clinical efficacy of mRNA 28 and BBIBP-CorV 29 vaccines in pwMS on S1PR modulators and aCD20, however, further replications are required to validate these findings.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that PI markedly enhances post-vaccine humoral and, and, to a lesser extent, cellular responses across DMTs, i.e. that the immunologic benefits of PI extended to patients on DMT classes -aCD20 and S1P -that are associated with attenuated postinfection [41][42][43] and post-vaccination responses 24,25 . Thus, vaccinated MS patients on aCD20 and S1P therapies who had prior COVID-19 infection -and these currently comprise the majority of patients in the US -likely have significantly better immune protection than would be expected based on published studies of vaccination-only immune responses 24,25,56 .…”
Section: Discussionmentioning
confidence: 99%
“…that the immunologic benefits of PI extended to patients on DMT classes - aCD20 and S1P - that are associated with attenuated post-infection 41-43 and post-vaccination responses 24, 25 . Thus, vaccinated MS patients on aCD20 and S1P therapies who had prior COVID-19 infection - and these currently comprise the majority of patients in the US – likely have significantly better immune protection than would be expected based on published studies of vaccination-only immune responses 24, 25, 56 . Moreover, our results suggest that it may be possible to improve humoral and cellular immune response defenses following repeated exposure to virus-specific antigens even in patients whose immune system has been partially compromised by medications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation